Epidemiology and Outcomes of Infected Non-Unions: An Observational Study at an Infectious Disease Referral Centre - Sara Tedeschi; Nicolò Rossi; Eleonora Zamparini; Simone Ambretti; Massimiliano Mosca; Cesare Faldini; Stefano Zaffagnini; Alessandra Maso; Andrea Sambri; Massimiliano De Paolis; Pierluigi Viale (Antibiotics)
Objectives: The main aim of this study was to describe the epidemiology of infected non-unions (INUs) managed at an Infectious Disease (ID) referral centre and to investigate the factors associated with treatment failure. Methods: This was an observational retrospective study on adult patients with INUs managed between 2012 and 2018 at the ID Unit of the IRCCS Azienda Ospedaliero-Universitaria di Bologna, an Italian ID referral centre for bone and joint infections. Patients were observed for at least 24 months. Those who achieved clinical success were compared with those who experienced clinical failure; to identify factors associated with treatment failure, we performed a univariate and multivariate logistic regression analysis. Results: Overall, 78 patients were included. A total of 57/78 (73%) were males; their median age was 43 (IQR 34–56) years; their median Charlson index was 0 (IQR 0–2); 32/78 (41%) reported a history of an open fracture; the non-union most frequently involved the leg. Polymicrobial infection was found in 23/78 cases (29%); the most common microorganisms were coagulase-negative staphylococci (n = 47) and Staphylococcus aureus (n = 35). At 24-month follow-up from index surgery, 16/78 patients had experienced clinical failure: 13 (16.6%) presented with persistence of local signs of infection and 3 (3.8%) had undergone amputation. Logistic regression analysis of risk factors for clinical failure identified body mass index (BMI) (aOR 1.15; 95% CI 1.03–1.28, p = 0.01) and MRSA infection (aOR 5.35; 95% CI 1.06–26.92, p = 0.04) as factors associated with clinical failure. Conclusions: Given that a standardized management of antibiotic therapy is initiated by an expert ID consultant team, BMI and MRSA infection are associated with worse outcomes among patients with INUs.